2017
DOI: 10.3390/cli5020030
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Long-Term Spatio-Temporal Rainfall Variability over Ghana using Wavelet Analysis

Abstract: Abstract:Rainfall variability has strong impact on food security, livelihood and socio-economic activities as farming in West Africa is mainly rain-fed. The annual, seasonal and decadal rainfall variability over Ghana has been studied and their periodicities analysed using wavelet analysis. A rainfall time series from 1901-2010 from the Global Precipitation Climatology Center (GPCC) was used in this analysis. It was observed that high mean annual rainfall totals ranging from 900-1900 mm are recorded over the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
63
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 49 publications
13
63
0
2
Order By: Relevance
“…is is because of the difficulty in forecasting rainfall in an area with erratic and varied rainfall pattern. Rainfall variability in the study area is also consistent with the findings of [45,46]. us, the fluctuations in the rainfall distribution on annual basis are not uncommon in the Savannah zone.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…is is because of the difficulty in forecasting rainfall in an area with erratic and varied rainfall pattern. Rainfall variability in the study area is also consistent with the findings of [45,46]. us, the fluctuations in the rainfall distribution on annual basis are not uncommon in the Savannah zone.…”
Section: Discussionsupporting
confidence: 87%
“…Having an increasing rainfall trend is quite a welcoming result for the residents in the area because of its potential agricultural, hydrological, and socioeconomic effects in an area that is highly populated by farmers, rain-fed agriculturalist for that matter. e increasing rainfall in the area supports the findings of [46] that found that, in the Savannah zone of Ghana, many of the years between 1901 and 2010 experienced above-normal rainfall in the area. Given that there is an upward trend in rainfall, farmers and the residents in general will be relieved especially in relation to water management towards future use.…”
Section: Discussionsupporting
confidence: 85%
“…These results are in agreement with the findings of previous independent works over the region [33][34][35][36][37]. The increase in precipitation from the Sahara to the humid equatorial zone was assumed to relate to a rapidly increasing depth of the moist layer equator-ward from the Intertropical Convergence Zone, ITCZ [33].…”
Section: Discussionsupporting
confidence: 91%
“…() and Baidu et al . (), to be a reliable, gauge‐based dataset over the study domain, and thus proves useful for comparison with GMet v1.0. GPCC datasets are monthly rainfall estimates covering the last century, and provided by the Earth System Research Lab (ESRL) at the National Oceanic and Atmospheric Administration (NOAA).…”
Section: Study Area and Data Sourcementioning
confidence: 96%
“…The use of Global Precipitation Climatology Centre (GPCC) datasets in this study stems primarily from the fact that, it has been demonstrated in various studies, for example Manzanas et al (2014) and Baidu et al (2017), to be a reliable, gauge-based dataset over the study domain, and thus proves useful for comparison with GMet v1.0. GPCC datasets are monthly rainfall estimates covering the last century, and provided by the Earth System Research Lab (ESRL) at the National Oceanic and Atmospheric Administration (NOAA).…”
Section: Global Precipitation Climatology Centre Datamentioning
confidence: 99%